ANALYSIS OF COMMUNITY AWARENESS IN MANAGING ORGANIC WASTE AS A SOLUTION TO OVERCOME FLOOD DISASTERS - Marsya Ainun Jariyah; Odi Tia Prastiti; Ayu Safira; Khansa Alia Faisyah; Novia Safitrih Betthan (JURNAL PENA SAINS, 2026)
This research is motivated by the frequent flooding in Laden Village, Pamekasan Regency, caused by a combination of factors: high rainfall, influx from other areas, and reduced water catchment areas due to dense settlements. The purpose of this study is to describe the conditions, causes, and impacts of flooding, as well as community and government efforts to mitigate them. This study employed descriptive qualitative research using questionnaires, interviews, and field observation methods. The study population included all residents living in the flood-prone area of Laden Village, Dusun Timur. The sample consisted of 10 purposively selected respondents, including affected residents and village officials in the flood-affected area. Field observations were conducted on September 27, 2025. Impacts experienced by the community included house damage, disruption to community activities, and an increased risk of environmental diseases. Our proposed mitigation effort involves promoting organic waste processing following the government's river dredging. The observations emphasize the importance of environmental management and spatial planning to reduce the risk of future flooding.